Clinical Efficacy of Dexmedetomidine and Propofol in Children Undergoing MRI for Urological Diseases: A Systematic Review: Dexmedetomidine and Propofol in Children Undergoing MRI for Urological Diseases - Shafiq, Pakeeza; Butt, Muhammad Umer Iqbal; Hassan, Hafiz Wajih Ul; Maqsood, Saba; Zaidi, Syed Imtiaz Ali; Ahmed, Aftab; Haq, Ehsan Ul (Pakistan Journal of Health Sciences, 2024)
Dexmedetomidine and propofol are commonly compared drugs used for sedation during pediatric anesthesia and Magnetic Resonance Imaging. However, their effectiveness and the impact on safety regarding children who undergo magnetic resonance imaging for specific urological diseases such as vesicoureteral reflux, hydronephrosis, and posterior urethral valves remain undetermined. Objectives: To evaluate the quality of sedation, recovery profiles, and complications using dexmedetomidine and propofol in pediatric patients undergoing magnetic resonance imaging for urological indications. Methods: Research with guidance from PRISMA was done in the PubMed, Google Scholar, and Semantic Scholar databases. Peer-reviewed articles that were published between January 2013 and April 2024 were identified bringing into the study 96 articles after applying the inclusion criteria. Cohort review: Fifteen studies were included in the present comparative analysis of dexmedetomidine and propofol for pediatric magnetic resonance imaging sedation. Results: Compared with propofol, dexmedetomidine provided better haemodynamic control, minimized emergence phenomenon and significantly improved postoperative recovery profiles. Nevertheless, the induction and recovery period was shorter in patients who received propofol. Both agents were associated with low adverse events incidences although subjects who received dexmedetomidine reported improved sedation quality that required less rescue medication than other subjects. Conclusions: It was concluded that dexmedetomidine and propofol are good in magnetic resonance imaging sedation for children with urological diseases, with better recovery and improved quality sedation from dexmedetomidine. Future research should extend the duration of intervention and make the dose-response relationship more precise.